(untitled) (مجلة المنصور, 2023)
As we all know Internet is a very widely used network, containing different types of multimedia, documents, programs and websites, for that reason it is difficult to maintain it as a malicious-free environment, these malicious codes are embedded into an innocent looking website, these websites in turn are very wide spread sites. An important feature a malicious code depends on reaching to as many users as it can get. This paper implemented generally to find and detect a malicious code in Internet websites, because of the wide spread of vandal users and malicious programs, the need for that tool has become a flat fact. A targeted website is analyzed for existing code and if that code is does not exist then its links are followed individually to check whether or not there is an indirect malicious code, this approach is useful in rapidly growing websites. The application is run on the server and when the client makes its request to load a website this request is sent first to the server then the system follows that on line to internet by (URL) and checks the contents of its website and follows all its sub-links in that website then if the website is clean (malicious free) then the client is granted access to that site, otherwise the system prints a warning message to the user containing the type of the malicious code and the time required to detect the infection.